Analisis Komunikasi Pemasaran dalam Pengumpulan Zakat, Infaq, Sedekah (Studi Kasus Baznas Kota Pontianak) - Aprianto, Aprianto; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this research is to find out Marketing Communication in implementing the Zakat, Infaq, and Sedekah Baznas programs in Pontaianak City. This study uses the Descriptive Qualitative Research method, with data collection techniques through in-depth interviews, observations, and documentation. The results of this research are that the Pontianak City Baznas uses a Marketing Communication approach to optimize the collection of Zakat, Infaq, and Sedekah (ZIS). The Pontianak City Baznas has begun to adopt digital technology, such as online payment platforms and application-based reporting systems, to simplify the ZIS payment process. However, the implementation is still in the early stages, so it has not been fully maximized. Obstacles in marketing communication are, lack of Zis literacy in the community, best-in-class human resources, competition with other Zis institutions. With the passage of time, the way people give zakat, infaq, and alms begins to change, both in traditional and modern ways. This strategy includes the following: social media, offline campaigns, strategic collaborations. The marketing communication strategy that is carried out shows an increase in ZIS fundraising every year, especially from young donor groups. The transparency of reports on the use of funds published through social media also increases public trust to contribute. marketing communication implemented by Baznas Pontianak City has an important role in the collection of Zakat, Infaq, and Sedekah (ZIS). The strategies used include various methods and communication media that aim to increase public awareness, expand the reach of target donors, and strengthen public trust in the institution.